2022
DOI: 10.3389/fonc.2022.1066557
|View full text |Cite
|
Sign up to set email alerts
|

Research landscape and trends of lung cancer radiotherapy: A bibliometric analysis

Abstract: Backgroundradiotherapy is one of the major treatments for lung cancer and has been a hot research area for years. This bibliometric analysis aims to present the research trends on lung cancer radiotherapy.MethodOn August 31, 2022, the authors identified 9868 articles on lung cancer radiotherapy by the Web of Science (Science Citation Indexing Expanded database) and extracted their general information and the total number of citations. A bibliometric analysis was carried out to present the research landscape, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…A major issue with chemo-RT is its toxicity associated with dose escalation, which severely limits its tumoricidal effect ( 33 , 71 ). This is best demonstrated by the result of RTOG 0617, which showed that the 74 Gy arm has shorter survival compared to the 60 Gy arm (20 vs. 29 months) due to increased toxicity and no benefit to the local control (LC) rate ( 33 , 71 ), so the trial had to be terminated early, and since then, the research focus has shifted to the optimization of chemo-RT. After ICI and SBRT each showing a survival benefit and tolerable toxicity profile when added to existing CCRT, the idea of a ‘quad-modality’ approach to LA-NSCLC treatment was proposed ( 33 , 72 , 73 ).…”
Section: Current Advances In Sbrt and Immunotherapies Synergy In Lung...mentioning
confidence: 99%
“…A major issue with chemo-RT is its toxicity associated with dose escalation, which severely limits its tumoricidal effect ( 33 , 71 ). This is best demonstrated by the result of RTOG 0617, which showed that the 74 Gy arm has shorter survival compared to the 60 Gy arm (20 vs. 29 months) due to increased toxicity and no benefit to the local control (LC) rate ( 33 , 71 ), so the trial had to be terminated early, and since then, the research focus has shifted to the optimization of chemo-RT. After ICI and SBRT each showing a survival benefit and tolerable toxicity profile when added to existing CCRT, the idea of a ‘quad-modality’ approach to LA-NSCLC treatment was proposed ( 33 , 72 , 73 ).…”
Section: Current Advances In Sbrt and Immunotherapies Synergy In Lung...mentioning
confidence: 99%
“…This method involves quantitative analysis of knowledge-based data derived from various sources, providing an objective overview of the research landscape, emerging trends, and hot topics within a specific area of study [ 21 ]. In doing so, bibliometric analysis offers a unique and comprehensive perspective that can assist researchers in understanding the progress in their field, as well as guide them in defining their own research paths [ 22 ]. Moreover, the information derived from a bibliometric analysis can be invaluable in helping researchers identify potential collaborators or suitable journals for publication.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some methodological limitations, the approach is used to visually quantify academic achievements and their impact in many fields. To date, several bibliometric studies related to LC have been published, mainly on immunotherapy ( 15 , 16 ), radiotherapy ( 17 ), gut microbiota ( 18 ), postoperative analgesia ( 19 ), anti-programmed death-1/programmed death-ligand 1 (anti-PD-1/PD-L1) therapy ( 20 ), machine learning in NSCLC radiotherapy ( 21 ), and chronic obstructive pulmonary disease ( 22 ). However, no bibliometric studies have been published in the NSCLC-Met field.…”
Section: Introductionmentioning
confidence: 99%